Entre casas e instituições escolares: a educação de Juazeirinho PB nas vozes de educadoras pioneiras (1950 -1973) - Costa, Kiara Tatianny Santos da (2012)
Our work focused on the prospect of studying about the history of education Juazeirinho, learning from the look of two pioneering educators, as this education was formed. Understanding how this educational history was made, realizing how it happened, saw the homes of school teachers and also under the most formalized with the advent of the institutionalization of education in the establishment of the school groups. This research was based in New Cultural History, oral history while addressing research methodology, they took care to make a cross between written sources, oral, and iconographic and practices aimed at establishing links between formal and informal teachers in educational spaces themselves and when he worked as a school using your home, establishing associations between educational practices that took place in different spaces, and understanding how women's participation was important for the establishment of education in the municipality. We understand how the performance of these pioneers became very relevant to the educational process site, which did not differ much from the education that is placed in the state during this period. Accordingly, the seizure of the memories of the teachers was interesting to notice how the performance of these, and non-formal education was responsible for this municipality could take the first steps in their educational development.